Time to focus on circulating nucleic acids for diagnosis and monitoring of gliomas: A systematic review of their role as biomarkers. (29th January 2021) - Díaz Méndez, Ana Belén; Tremante, Elisa; Regazzo, Giulia; Brandner, Sebastian; Rizzo, Maria G.
Abstract: Gliomas are diffusely growing tumours arising from progenitors within the central nervous system. They encompass a range of different molecular types and subtypes, many of which have a well‐defined profile of driver mutations, copy number changes and DNA methylation patterns. A majority of gliomas will require surgical intervention to relieve raised intracranial pressure and reduce tumour burden. A proportion of tumours, however, are located in neurologically sensitive areas and a biopsy poses a significant risk of a deficit. A majority of gliomas recur after surgery, and monitoring tumour burden of the recurrence is currently achieved by imaging. However, most imaging modalities have limitations in assessing tumour burden and infiltration into adjacent brain, and sometimes imaging is unable to discriminate between tumour recurrence and pseudo‐progression. Liquid biopsies, obtained from body fluids such as cerebrospinal fluid or blood, contain circulating nucleic acids or extracellular vesicles containing tumour‐derived components. The studies for this systematic review were selected according to PRISMA criteria, and suggest that the detection of circulating tumour‐derived nucleic acids holds great promises as biomarker to aid diagnosis and prognostication by monitoring tumour progression, and thus can be considered a pathway towards personalized medicine. Abstract : This systematic review, performed according to PRISMA criteria, discusses the increasing role and the potential of circulating nucleic acids (cfNAs) as glioma markers that can be obtained with minimal invasiveness. The studies here reviewed suggest that the detection of tumour‐derived cfNAs holds great promises as biomarker to aid diagnosis and prognostication by monitoring tumour progression, and thus can be considered a pathway towards personalized medicine.